Design Of Power Amplifier For Radio Over Fiber Technology (ROF) - Arisita Duwi, Sapit (UTeM, 2010)
Based on wireless network radio over fiber (RoF) technology has been proposed as a promising cost effective solution to meet ever increasing user bandwidth and wireless demands. In this network, a central station (CS) is connected to numerous functionally simple radio access point (RAP) via an optical fiber. The only components required at the passive RAP are electro absorption modulator (EAM) and antenna where EAM is used as a remote transceiver. There are practical limitations on the power that can produce by the passive RAP which can affect the dynamic range. In order to improve the dynamic range of passive picocell (RAP), the power amplifier is placed between the EAM and the antenna. The aim of this project is to design power amplifier for radio over fiber technology with short range application (picocell) which operating at 5.2 GHz, with power amplifier gain above 10 dB and required to achieve transmit power below 30 dBm. Picocells use power lower than 1 Watt (30 dBm). The transistor used for power amplifier design is Agilent ATF-55143 because it met all of the requirements for the target specifications. Microwave Office Software is used in power amplifier design simulation. In the simulation, the analyses of scattering parameters are concerned which presents the gain, power output and efficiency of power amplifier. From the simulation results; gain is 12.17 dB, power output is 25.07 dBm and efficiency is 23.01%. At the end of design, the power amplifier is purposed as a RF front end of RAP for RoF technology.